NEW CHROMOSOME COUNTS OF BERBERIS L. (BERBERIDACEAE) SUGGEST THAT POLYPLOIDY DOES NOT PLAY A SIGNIFICANT ROLE IN THE DIVERSIFICATION OF THE GENUS IN THE NEPAL HIMALAYA - Adhikari, B.; Pendry, C. A.; Möller, M. (Edinburgh Journal of Botany, 2014)
Chromosomes were counted for nine of the 24 taxa of Berberis (Berberidaceae) from Nepal, five of which were counted for the first time. The results show that all these species have somatic chromosome numbers of 2n = 28. The absence of polyploids suggests that polyploidy may not have been a major driver of speciation and diversification of Berberis in the Nepal Himalaya.